A Chronology of Historical Events in the Iraqi Oil and Gas Industry for the Period (1980-2010) - Faleh Ghali, Assist. Lect . Israa (Basra studies journal, 2025)
The oil and gas industry is one of the fundamental pillars of the Iraqi economy and the main source of public revenue. This vital sector underwent a series of significant challenges and transformations during the period from 1980 to 2010 due to political, economic, regional, and international circumstances. Iraq experienced several wars during these decades, beginning with the Iran-Iraq War in the 1980s, followed by the Gulf War in 1991, and then the U.S. invasion in 2003, all of which caused severe damage to the infrastructure of the oil sector. Additionally, Iraq subjected to harsh economic sanctions during 1990s, which negatively affected its production capabilities and refining sectors, leading to a sharp decline in domestic output. Despite these challenges, Iraq’s vast reserves of oil and gas have kept it among the world’s major oil producers. Following 2003, Iraq began restructuring its oil sector by opening the door to foreign investment. Numerous contracts were signed with international companies to explore and develop oil fields, contributing to a noticeable improvement in production levels. However, the sector continues to face persistent challenges such as weak infrastructure, global oil price fluctuations, the need for better management of oil revenues, and the development of the gas sector. This study aims to trace the development of the oil and gas industry in Iraq from 1980 to 2010, focusing on the challenges faced by the sector, the opportunities for performance improvement, the policies adopted for its management, and prospects for a sustainable energy transition in the future.